Respuesta :

Answer:

-t*(t -16) ≥ 39

-t*(t -16)  = 39

t = 3 or 13 hours

Step-by-step explanation:

When number of people is at 39 or more means the number of people of greater than or equal to 39.

 So, the inequality is,

          -t*(t -16) ≥ 39

When the number of people is 39, the equation is,

     -t*(t - 16) = 39

     -t²+ 16t   = 39

0 = 39 + t² - 16t

t² - 16t + 39 = 0

Sum = -16

Product = 39

Factors = -3 , -13   [ (-3) * (-13) = 39  & (-3) +(-13) = -16 ]

Rewrite the middle term using the factors.

t² - 3t - 13t + 39 = 0

t(t -3) - 13(t - 3) = 0

(t -3)( t - 13)     = 0

     t -3 = 0     ; t- 13 = 0

          t = 3  or  t = 13

t = 3 hours or 13 hours.